HPLC Method for the Simultaneous Estimation of Aspirin and Omeprazole in their New Combination. Issue 3 (4th May 2017) - Nassar, Mohammed W.I.; Attia, Khalid A.M.; Mohamed, Ahmed A.; Shahin, Mohamed
Abstract: A simple, sensitive, accurate and precise RP-HPLC method was developed for simultaneous estimation of aspirin and omeprazole in bulk powder and pharmaceutical formulation. The separation process was developed under optimized chromatographic conditions using a reversed phase of C18 column and a mobile phase consists of acetonitrile-water (60:40 v/v) adjusted to pH 2.9 with o -phosphoric acid. The flow rate used was 1 ml/min and UV detection at 240 nm. The retention time of aspirin and omeprazole was found to be 3.076 and 5.329 min respectively. The method was found to be linear over a concentration range of 10-100 μg/ml and 4-80 μg/ml for aspirin and omeprazole, respectively. The method was validated according to ICH guidelines and the results were satisfactory. Hence, the proposed method could be applied for the routine quality control analysis of this new combination in pure powder and pharmaceutical formulation.